2018
DOI: 10.1186/s40693-018-0079-4
|View full text |Cite
|
Sign up to set email alerts
|

Frugivory and seed dispersal in the endemic cactus Eulychnia acida: extending the anachronism hypothesis to the Chilean Mediterranean ecosystem

Abstract: Background: Eulychnia acida is an endemic Chilean cactus species whose fruits show several traits that, taken as a whole, are compatible with a seed dispersal syndrome by large herbivore vertebrates. Since only a few large native mammals exist in Chile at present, cactus fruit consumption and seed dispersal may be coopted by introduced mammals as predicted by Janzen and Martin's (1982) hypothesis for tropical ecosystems. Findings: We describe the current frugivore species of E. acida in a protected semiarid-Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…For instance, when fox losses were completely compensated with badgers, seed dispersal into Mediterranean scrubland increased to a level that even surpassed the baseline scenario. Similar compensation has been documented not only among native seed dispersers (Cordeiro andHowe 2003, Zhou et al 2013) but also by introduced and domestic species (García et al 2014, Cares et al 2018, Muñoz-Gallego et al 2019. However, such apparent compensation could be less complete if disperser species differ in subtle but key aspects of the seed dispersal process (e.g.…”
Section: The Effects Of Defaunation and Density Compensation On Seed supporting
confidence: 58%
“…For instance, when fox losses were completely compensated with badgers, seed dispersal into Mediterranean scrubland increased to a level that even surpassed the baseline scenario. Similar compensation has been documented not only among native seed dispersers (Cordeiro andHowe 2003, Zhou et al 2013) but also by introduced and domestic species (García et al 2014, Cares et al 2018, Muñoz-Gallego et al 2019. However, such apparent compensation could be less complete if disperser species differ in subtle but key aspects of the seed dispersal process (e.g.…”
Section: The Effects Of Defaunation and Density Compensation On Seed supporting
confidence: 58%
“…Our study demonstrates that both goats and pine martens are effective seed dispersers of C. humilis in Mallorca, and we thus hypothesize that these introduced frugivores, especially the goat, could be replacing the function probably carried out by the extinct M. balearicus in the past, acquiring the role of seed dispersal "rescuers". This role has already been suggested for the goat in other systems (e.g., Mancilla-Leytón et al, 2015;Cares et al, 2018). So, despite the fitness costs imposed by both introduced mammals, they could be providing an indispensable service to this ancient palm by dispersing it on island systems, where native dispersers are extinct and the alternatives are very limited.…”
Section: Total Seed Dispersal Effectiveness (Sde)mentioning
confidence: 73%
“…Given that humans are largely determining the number of goats on Mallorca (Mayol et al, 2017), they are probably influencing the "relative seed dispersal effectiveness", not only for C. humilis, but also for many other systems where livestock "rescues" the seed dispersal service of anachronistic plant species (Janzen and Martin, 1982;Cares et al, 2018). Goats have been described to expel the ingested seeds while defecating (e.g., Mancilla-Leytón et al, 2011) or ruminating (e.g., Delibes et al, 2017a); however, we found no goat feces with C. humilis seeds in our study sites.…”
Section: Quantitative Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…The Peruvian E. ritteri is clearly retrieved as an isolated, early lineage of Eulychnia and cannot go back to recent long‐distance dispersal. However, an early‐dispersal event cannot be ruled out, in particular considering the large, juicy fruits of some Eulychnia taxa, which may in the past have been dispersed by now extinct herbivore mammals (Cares et al, 2018). The guanaco ( Lama guanicoe ), for example, once widespread from northern Peru to Tierra del Fuego but now distributed in less than 30% of its range at the time of arrival of Europeans to South America (Marin et al, 2013 and references therein), may have acted as an important disperser of Eulychnia seeds.…”
Section: Discussionmentioning
confidence: 99%